Chinese energy futures and their implications for the United States - Eberling, George (Lexington Books, 2011)
"Shows how China will most likely address its growing oil energy dependence. Eberling's study uses scenario analysis and the PRINCE model to determine what will be the most likely U.S. foreign policy consequences, stemming from the most current literature available on energy security and foreign policy. Chinese Energy Futures also contributes to the literature on Chinese and United States energy security, foreign policy, political economy, and political risk analysis."--Publisher's description.